Long non-coding RNAs (lncRNAs) and their transcriptional control of inflammatory responses - Mathy, Nicholas W. (J Biol Chem, 2017)
Long non-coding RNAs (lncRNAs) have emerged as potential key regulators of the inflammatory response, particularly by modulating the transcriptional control of inflammatory genes. lncRNAs may act as an enhancer or suppressor to inflammatory transcription, function as scaffold molecules through interactions with RNA-binding proteins in chromatin remodeling complexes, and modulate dynamic and epigenetic control of inflammatory transcription in a gene-specific and time-dependent fashion. Here, we will review recent literature regarding the role of lncRNAs in transcriptional control of inflammatory responses. Better understanding of lncRNA regulation of inflammation will provide novel targets for the development of new therapeutic strategies.